THE FLOURISHING LEVEL AND WILLINGNES TO SPEAK ENGLISH OF ENGLISH LANGUAGE DEPARTMENT STUDENTS - Giyanes Swara; Rita Hayati (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Having a high level of emotional, psychological, and social well-being is the definition of flourishing. The role of flourishing has also started to be studied in the field of education The goals of this study were to determine the relationship and contribution between students' flourishing levels and their willingness to speak (WTS). In this study, 73 sixth-semester students of English language department of a state university in South Sumatera were were chosen as a sample using the purposive sampling approach. To collect data, two types of questionnaires are used: (1) the Flourishing Scale (FS) Questionnaire and (2) the Willingness to Speak (WTS) Questionnaire. The Pearson correlation coefficient was utilized to investigate the relationship between student flourishing and WTS, while the regression coefficient was employed to determine the contribution. The data revealed that flourishing and WTS were moderately and positively associated. The largest contribution that came from the students' flourishing levels was 21.4%.